Tensile strength of unsaturated coarse and fine-grained soils - Bulolo, Sam (2022)
Soils at the ground surface experience multiple cycles of drying and wetting. On drying, the soils experience shrinkage and cracks may appear. The development of cracks depends on the tensile strength of the soil. Such cracks increase the permeability of the soil and can cause slopes and earth structures to fail due to rainfall. Several tensile strength models have been proposed for unsaturated soils considering the effect of matric suction. However, the tensile strength models proposed are for either cohesionless (coarse-grained) or clayey (fine-grained) soils. The tensile strength models were shown to be different in their definition of suction stress and the presence or absence of a cohesion term. As tensile strength data of fine-grained soils with the same soil structure and soil–water characteristic curve (SWCC) data are lacking in the literature, Brazilian tensile tests and SWCC tests were conducted on compacted fine-grained soils from two residual soil formations. The test data highlighted the problem in the friction angle used in existing tensile strength models. Using a general form of the suction stress and the extended Mohr–Coulomb criterion with the Brazilian test Mohr circle, a new tensile strength model applicable to both coarse-grained and fine-grained soils was proposed. The proposed model was shown to perform better than existing models using independent data.